A Study of Incidence of Pre-Eclampsia in Relation to Maternal Age (International Journal of Physiology, 2021)
Background: - Pre-eclampsia is a serious complication of pregnancy and contributes significantly maternalas well as perinatal morbidity and mortality. So this study is done to find if there exists any relationshipbetween maternal age and pre-eclampsia.Aim:- To study what age group is more prone to development of pre-eclampsia in normal pregnancies.Methodology:- 400 pre-eclamptic women in age group 18-42 years were included in the study. Cases aredivided according to different age group.Result:- Higher incidence of pre-eclampsia was observed in the age group 18-26 years followed by 35-42years.Discussion:- Age is found to be related to pre-eclampsia.Conclusion:- From this study, this can be concluded that age less than 25 years and age greater than 35 yearsare more prone to development of pre-eclampsia.